Functional outcome of operative management of Haglund deformity in non-athletic individuals-a case series - Supe, Amit Chandrakant; Singh, Prince; Pawar, Eknath Deosing; Kolur, Shivaprasad Sharangouda; Topno, Rohit; Pande, Kartik (International Journal of Research in Orthopaedics, 2024)
Haglund’s deformity is a symptomatic osseous outgrowth or prominence of the posterolateral corner of calcaneus usually in young individuals which presents in the form of posterior heel pain, sometimes intractable in chronic cases, which aggravates on walking or on dorsiflexion of the foot and is relieved with rest and anti-inflammatory medications in the initial phases. Management involves an initial conservative trial involving lifestyle changes and medical management, failure of which warrants surgical management for symptomatic relief along with ability to return to perform activities of daily living. We have a series of 4 patients with a Haglund’s deformity who presented to us with chronic posterior heel pain of varying duration with episodic exacerbations who were initially managed with a conservative trial with medications, physiotherapy, lifestyle modifications, usage of soft silicon sole for the footwear; the failure of which prompted us to go ahead with surgical management of these patients-all 4 patients were managed with a lateral wedge removal of the calcaneus with excision of the retrocalcaneal bursa. All 4 patients reported significant improvement in the symptoms with adequate postoperative care and rehabilitation. As we have seen in this case series of 4 patients presented here, Haglund’s deformity which is a part of a larger Haglund’s syndrome, has a chronic progression over a period of time with episodic exacerbations and remissions, which could be managed conservatively for a significant period initially but, if need be, surgical management should not be deferred not only to provide symptomatic relief as a major goal, but also to avoid permanent degenerative damages to the concerned soft tissues.